Adverse Outcome in COVID-19 Is Associated With an Aggravating Hypo-Responsive Platelet Phenotype - Schrottmaier, Waltraud C.; Pirabe, Anita; Pereyra, David; Heber, Stefan; Hackl, Hubert; Schmuckenschlager, Anna; Brunnthaler, Laura; Santol, Jonas; Kammerer, Kerstin; Oosterlee, Justin; Pawelka, Erich; Treiber, Sonja M.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Thromboembolic complications are frequently observed in Coronavirus disease 2019 (COVID-19). While COVID-19 is linked to platelet dysregulation, the association between disease outcome and platelet function is less clear. We prospectively monitored platelet activation and reactivity in 97 patients during the first week of hospitalization and determined plasma markers of platelet degranulation and inflammation. Adverse outcome in COVID-19 was associated with increased basal platelet activation and diminished platelet responses, which aggravated over time. Especially GPIIb/IIIa responses were abrogated, pointing toward impeded platelet aggregation. Moreover, platelet-leukocyte aggregate formation was diminished, pointing toward abrogated platelet-mediated immune responses in COVID-19. No general increase in plasma levels of platelet-derived granule components could be detected, arguing against platelet exhaustion. However, studies on platelets from healthy donors showed that plasma components in COVID-19 patients with unfavorable outcome were at least partly responsible for diminished platelet responses. Taken together this study shows that unfavorable outcome in COVID-19 is associated with a hypo-responsive platelet phenotype that aggravates with disease progression and may impact platelet-mediated immunoregulation.